Fishing for Catalysts: Mechanism-Based Probes for Active Species in Solution - Adlhart, Christian; Chen, Peter (Helvetica chimica acta, 2000)
A combination of derivatization with charged substrates and electrospray‐ionization mass spectrometry is used to fish out the active species in a catalytic reaction. The observed species in the mass spectrometer corresponds to the resting state of the catalyst. Data for the ring‐opening metathesis polymerization (ROMP) of norbornene by (Cy3P)2Cl2Ru=CHPh (Cy=cyclohexyl) are used to illustrate the method.